Respiratory Severity Score with Regard to Birthweight during the Early Days of Life for Predicting Pulmonary Hypertension in Preterm Infants. (2nd April 2020) - Seo, Yu Mi; Yum, Sook Kyung; Sung, In Kyung
Abstract: Objective: The respiratory severity score (RSS) has been demonstrated to be associated with the oxygenation index in intubated newborn infants. We aimed to evaluate the usefulness of RSS with regard to birthweight (BW) in preterm infants for predicting an association with future pulmonary hypertension (PH). Methods: Preterm infants with <30 weeks' gestation and <1250 g BW were reviewed and grouped into two (PH vs. no PH). Basic perinatal characteristics, comorbidities and parameters reflecting lung condition, including duration of invasive mechanical ventilator care, were compared. Respiratory support parameters (FiO2, RSS and RSS/kg) during the first 5 days of birth (0–120 h) were compared between the groups, and receiver operating characteristics curves were produced to evaluate the association with PH. Results: RSS/kg, of the three respiratory support parameters, demonstrated significantly higher values in the PH group in the early days of life. Particularly, RSS/kg at day 2 of life had the greatest area under the curve [0.762, 95% confidence interval (CI) 0.655–0.869, p < 0.001] and maintained statistical significance [odds ratio (OR) 1.352, 95% CI 1.055–1.732, p = 0.017] in the multivariable analysis for a potential association with PH, along with gestational age (OR 0.996, 95% CI 0.993–0.999, p = 0.015) and preterm premature rupture of membrane >18 h (OR 4.907, 95% CI 1.436–16.765, p = 0.011). Conclusion: RSS/kg is a potential marker associated with the development of PH. Future studies could verify its usefulness as a reliable surrogate for predicting respiratory morbidity in clinical settings.